Abdominal Abscesses and Destruction of Inguinal Canal with Mesh Dislocation caused by a Perforated Diverticulitis - Christoph Paasch; Franziska Renger; Sergej Baschinskij; Martin W. Strik (Case Reports in Surgery)
The diverticulitis is a frequent disease of the gastrointestinal tract. It may lead to a variety of severe complications. In some cases, it has to be surgically treated. Herein, we present a rare case of a 66-year-old man, who suffered from a painful, visible “fist sized” mass of the left lower abdomen. A perforated diverticulitis with abdominal, cutaneous abscesses and destruction of the inguinal canal with mesh dislocation was diagnosed and successfully surgically treated.